Analysis of Sharia Compliance Implementation in Assessing the Performance of Agent of PT Asuransi Jiwa Syariah Bumiputera - Nasution, Nurdin; Marliyah, Marliyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Sharia compliance is one of the elements in the assessment of the soundness level of Sharia Insurance. Maintenance of the health level of insurance will be directly proportional to the maintenance of public trust so if insurance is negligent in maintaining its health level because it does not apply Sharia principles, public trust in insurance will be lost. This study aims to analyze the implementation of Sharia Compliance in assessing the performance of PT Asuransi Jiwa Syariah Bumiputera Agents. The performance of Sharia Insurance Agents certainly needs to be assessed whether it is in accordance with Sharia compliance. The method used in this research is descriptive qualitative. The results of this study indicate that the Insurance Agent of PT Asuransi Jiwa Syariah Bumiputera has carried out marketing in accordance with Sharia compliance, only that the company’s operational system is still under the auspices of its parent, so it cannot be ascertained that it will be free from elements of ribawi.